Shedding light on the effects of 1, 25-dihydroxyvitamin D3 on epidermal lipid barrier formation in three-dimensional human skin equivalents. Issue 189 (May 2019) - Mieremet, Arnout; van Dijk, Rianne; Gooris, Gert; Bouwstra, Joke A.; El Ghalbzouri, Abdoelwaheb
Highlights: Epidermal barrier formation of human skin equivalents is compromised. In vitro addition of 1, 25(OH)2 D3 activated vitamin D signalling pathway. Epidermal morphogenesis was unaffected after VDR activation. Antimicrobial peptide LL37 was upregulated in vitro . Lipid barrier formation remained similar after addition of 1, 25(OH)2 D3 . Abstract: Human skin equivalents (HSEs) are three dimensional models resembling native human skin (NHS) in many aspects. Despite the manifold similarities to NHS, a restriction in its applications is the altered in vitro lipid barrier formation, which compromises the barrier functionality. This could be induced by suboptimal cell culturing conditions, which amongst others is the diminished activation of the vitamin D receptor (VDR) signalling pathway. The active metabolite of this signalling pathway is 1, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ). An interacting role in the formation of the skin barrier has been ascribed to this pathway, although it remains unresolved to which extent this pathway contributes to the (mal-)formation of the epidermal barrier in HSEs. Our aim is to study whether cell culture medium enriched with 1, 25(OH)2 D3 affects epidermal morphogenesis and lipid barrier formation in HSEs. Addition of 20 nM 1, 25(OH)2 D3 resulted in activation of the VDR signalling pathway by inducing transcription of VDR target genes (CYP24A and LL37) in keratinocyte monocultures and in HSEs. Characterization of HSEs supplemented with 1, 25(OH)2 D3 using immunohistochemical analyses revealed a high similarity in epidermal morphogenesis and in expression of lipid processing enzymes. The barrier formation was assessed using state-of-the art techniques analysing lipid composition and organization. Addition of 1, 25(OH)2 D3 did not alter the composition of ceramides. Additionally, the lateral and lamellar organization of the lipids was similar, irrespective of supplementation. In conclusion, epidermal morphogenesis and barrier formation in HSEs generated in presence or absence of 1, 25(OH)2 D3 leads to a similar morphogenesis and comparable barrier formation in vitro .